IMPLEMENTASI MEDIA BHINNECARD MODEL TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN PENDIDIKAN PANCASILA DI SMPN 1 REMBANG - Salsabila Kurnia; Siti Awaliyah; Nur Wahyu Rochmadi (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study was motivated by the low learning outcomes of students in Pancasila Education at SMPN 1 Rembang, which were caused by teacher-centered learning practices and the limited use of innovative and interactive instructional media. The study aimed to improve students’ learning outcomes through the implementation of BhinneCard media integrated with the Teams Games Tournament (TGT) learning model. This research employed a quantitative approach using Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 32 students of class VIII A at SMPN 1 Rembang in the 2025/2026 academic year. Data were collected through observation, tests, documentation, and student response questionnaires. The findings revealed that the implementation of BhinneCard media combined with the Teams Games Tournament (TGT) model significantly improved students’ learning outcomes in Pancasila Education. In the first cycle, the average student score reached 74.06 with a learning mastery percentage of 71.87%. After improvements were made in the second cycle, the average score increased to 86.56 with a mastery percentage of 90.62%. In addition to improving learning outcomes, the use of BhinneCard media also enhanced students’ participation, group collaboration, and self-confidence during the learning process. Therefore, the implementation of BhinneCard media with the Teams Games Tournament (TGT) model was proven effective in creating an active, collaborative, interactive, and enjoyable learning environment in Pancasila Education. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar murid pada mata pelajaran Pendidikan Pancasila di SMPN 1 Rembang akibat pembelajaran yang masih berpusat pada guru serta kurangnya penggunaan media pembelajaran yang inovatif dan interaktif. Penelitian ini bertujuan untuk meningkatkan hasil belajar murid melalui implementasi media BhinneCard dengan model pembelajaran Teams Games Tournament (TGT). Penelitian menggunakan pendekatan kuantitatif dengan jenis Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian terdiri atas 32 murid kelas VIII A SMPN 1 Rembang tahun ajaran 2025/2026. Teknik pengumpulan data dilakukan melalui observasi, tes, dokumentasi, dan angket respon murid. Hasil penelitian menunjukkan bahwa penggunaan media BhinneCard model Teams Games Tournament (TGT) mampu meningkatkan hasil belajar Pendidikan Pancasila secara signifikan. Pada siklus I, nilai rata-rata hasil belajar murid mencapai 74,06 dengan persentase ketuntasan sebesar 71,87%. Setelah dilakukan perbaikan pada siklus II, nilai rata-rata meningkat menjadi 86,56 dengan persentase ketuntasan mencapai 90,62%. Selain meningkatkan hasil belajar, media BhinneCard juga mampu meningkatkan keaktifan, kerja sama kelompok, serta kepercayaan diri murid selama proses pembelajaran berlangsung. Dengan demikian, implementasi media BhinneCard model Teams Games Tournament (TGT) dinyatakan efektif dalam menciptakan pembelajaran Pendidikan Pancasila yang aktif, kolaboratif, interaktif, dan menyenangkan.